The association between different insulin resistance surrogates and all-cause mortality and cardiovascular mortality in patients with metabolic dysfunction-associated steatotic liver disease - Xin Gao; Tianyi Chen; Feilong Zhou; Yanmei Sun; Jiaqi Zhang; Xinhao Li; Weijie Zhao; Yunxin Li; Yanlong Shi; Kaiyi Niu; Yizhu Wang; Yewei Zhang; et al. (Cardiovascular Diabetology)
Abstract Background Metabolic dysfunction-associated steatotic liver disease (MASLD) is closely associated with insulin resistance (IR). However, the prognostic value of different alternative IR surrogates in patients with MASLD remains unclear. This study aimed to evaluate the association between various IR indices and all-cause mortality and cardiovascular mortality in MASLD patients. Methods A total of 8,753 adults aged ≥ 20 years with MASLD from the National Health and Nutrition Examination Survey (NHANES, 2003–2018) were included, and their mortality data were obtained from the National Death Index (NDI). Insulin resistance surrogates [including the triglyceride-glucose (TyG) index, TyG-body mass index (TyG-BMI), TyG-waist circumference index, TyG-waist-to-height ratio index, and Homeostatic Model Assessment for IR] were stratified into quartiles. Cox proportional hazards models, receiver operating characteristic (ROC) curve analysis, restricted cubic spline (RCS), mediation analyses, and subgroup analyses were used to explore the associations between these indices and all-cause mortality as well as cardiovascular mortality in MASLD patients. Results During a median follow-up of 98 months, 1,234 deaths were observed, including 409 cardiovascular disease (CVD)-related deaths. In the fully adjusted model, higher quartiles of TyG-related indices were significantly associated with an increased risk of all-cause mortality in MASLD patients. Furthermore, the TyG-BMI index was associated with both all-cause mortality and CVD mortality [all-cause mortality: HR (95% CI) 2.84 (1.73–4.67), P < 0.001; CVD mortality: HR (95% CI) 5.32 (2.26–12.49), P < 0.001]. The RCS analyses indicated a U-shaped relationship between TyG-BMI and mortality, with a threshold value of 270.49. Subgroup analyses demonstrated that TyG-related indices had stronger associations with mortality in elderly MASLD patients. Conclusions Our findings highlight the prognostic value of IR indices, particularly TyG-BMI index, in predicting all-cause mortality and CVD mortality in MASLD patients. Graphical abstract This study highlights the prognostic value of IR indices, particularly TyG-BMI index, in predicting all-cause mortality and CVD mortality in MASLD patients.